Achieving gender equity targets within selected private hospitals, Gauteng Province, South Africa - Mathevula, B. M.; Rachidi, M. F. (International Conference on Public Administration and Development Alternatives (IPADA), 2020)
Gender equity, the fifth goal of the United Nations' 2030 Agenda Sustainable Development, is vital for women empowerment. The importance of gender equity in development has led to diverse treaties, which have been entered into. South Africa, as part of these accords, is also promoting empowerment of women. Although there is progress towards achievement of gender equity targets, that progress is not enough. Despite the fact that the health sector, public or private, has more female employees than males, leadership and management positions are still dominated by more males than females. In view of this problem, the objective of this paper is to examine the progress made by the selected private hospitals in Gauteng Province, as well as the challenges these hospitals face in trying to achieve gender equity. A qualitative method was used in which human resources managers, as well as hospital managers from selected private hospitals were interviewed. Data were collected through individual, face-to-face interviews to explore the progress made towards achieving gender equity targets, the hospitals' commitment to gender equity and challenges that they face in trying to achieve gender equity. The results of the study suggest that progress has been made by the selected hospitals in empowering women. However, a lot of work still needs to be effected. The challenges pointed out to the dynamics that the management systems of the hospitals can address, as well as effort needed from the women managers themselves. This paper recommends that women empowerment and achievement of gender equity targets need concerted effort from different stakeholders. In addition, further research needs to be conducted to find out what mechanisms can be put into place to help boost women's self-confidence in terms of grabbing leadership opportunities. Keywords: Gender equity, Leadership, Management, Women empowerment, Sustainable development
Journal article published in The International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Gender equity; Leadership; Management; Women empowerment; Sustainable development; Sex discrimination; Sustainable development -- South Africa